Influencia del deficiente soporte familiar en la salud del adulto mayor perteneciente al programa de UPA (unidad primaria de atención al adulto) en Essalud - Hospital I La Esperanza. - Córdova Sandoval, Hilda Elizabeth (2016)
This thesis was performed with the purpose to explain the influence of family support in the health of the Older Adult belonging to the Program of UPA (Primary Unit of Attention to adult) in ESSALUD - Hospital I hope: 2015. It has been considered to be the kind of applied research, taking as a basis a explanatory design has been used the methods and techniques of qualitative and quantitative research and the sample consisted of 44 Older Adults Program Users of UPA (Primary Unit of Attention to adult) in ESSALUD - Hospital I hope. The results obtained can be deduced that these people have lack of family support, decrease of family integration, poor interpersonal relationships in their family environment and family abandonment that negatively affect the quality of their physical and mental health. These findings show the need for the government to strengthen the institutions of support and assistance to the elderly; mainly in places intended for health promotion, healthy life styles and recreation for the integral development of the older adult.